Topic : Linear equations in two variables.
Given :
- 2x - y = 3 ––– (i)
- - x - y = 3 ––– (ii)
Solution :
Now,
(i) – (ii)
Now, substituting the value of x in Eq (i) :
Therefore,
- <u>The value of x = 0 and y = -3</u>
Answer:
x = 6
y = 9
This is the correct answer. Not satisfied? Check out this answer expert verified answer of the same question but with a step-by-step explanation. This answer is just a simple version of rocioo's correct answer.
Expert Verified Answer (of this same question but with a step-by-step explanation):
This is the link to rocioo's answer. <u>brainly.com/question/13675950</u>
Answer:
what are u trying to ask
Step-by-step explanation: